Pengembangan Pupuk Cair Nitrogen Berukuran Nanometer untuk Meningkatkan Efisiensi Pemupukan - Deden Saprudin; Munif Gulamahdi; Wiwik Hartatik; Latifah Kosim Darusman; Ilfa Nuraisyah (Jurnal Ilmu Pertanian Indonesia, 2012)
Conventional utilization of urea just has absorbed 30-60%. Remaining, 40-70% lost to environment, give not economic benefit and serious problem in environment. The use of less efficient urea has received attention lately. One way to overcome the problem of inefficiency of urea fertilizer use is a nano-sized fertilizer. Synthesized nanofertilizer in this study were nanomagnetit (Fe3O4). Nanomagnetit synthesized from FeCl3 as a source of iron, sodium citrate as the reductant, and urea as a source base. Nanomagnetite synthesized using a hydrothermal method. Based on the results of X-ray diffraction, the nanomagnetit has average crystal size 46.66 nm and crystal structure is Face Center Cubic. Energy-dispersive X-ray spectroscopy shows constituent elements in nanomagnetite are iron (29.45%), oxygen (53.07%), carbon (14.86%), and sodium (2.62%). This shows the iron and oxygen is the main constituent elements nanomagnetite. In the process of magnetite formation absorbed urea by 30% with N content (0.14%) and most are in the liquid synthesis (0.82%) so that it can be used as fertilizer on crops. Based on this research, variations of pH (6-8) liquid fertilizer provided no significant effect. The addition of 0.15 g nanomagnetite have better growth among other treatments.